Long‐term Intrinsic Rhythm Evaluation in Dogs with Atrioventricular Block. (17th November 2015) - Santilli, R.A.; Porteiro Vázquez, D.M.; Vezzosi, T.; Perego, M.
Abstract : Background: Atrioventricular block (AVB) is a conduction abnormality along the atrioventricular node that, depending on etiology, may lead to different outcomes. Objectives: To evaluate variations of intrinsic rhythm (IR) in dogs that underwent pacemaker implantation (PMI). Animals: Medical records of 92 dogs affected by 3rd degree atrioventricular block (3AVB), advanced 2nd degree AVB (2AVB), paroxysmal 3AVB, 2:1 2AVB, or 3AVB with atrial fibrillation (AF) were retrospectively reviewed. Method: The patient IR was documented with telemetry on the day of 1 – (95% CI, 1–2), 33 – (95% CI, 28–35), 105 – (95%CI, 98–156), and 275 days (95%CI, 221–380) after PMI. According to AVB grade at different examinations, AVB was defined as progressed, regressed, or unchanged. Results: In 48 dogs, 3AVB remained unchanged, whereas in 7 it regressed. Eight cases of 2AVB progressed, 3 regressed and 2 remained unchanged. Eight cases of paroxysmal 3AVB progressed and 3 remained unchanged. Four dogs affected by 2:1 2AVB progressed, 2 regressed, and 1 remained unchanged. All cases with 3AVB with AF remained unchanged. Regression occurred within 30 days after PMI, whereas progression was documented at any time. Variations in IR were associated with type of AVB ( P < .03) and time of follow‐up ( P < .0001). Conclusions and clinical importance: The degree of AVB assessed at the time of PMI should not be considered definitive because more than one‐third of the cases in this study either progressed or regressed. Additional studies would be necessary to elucidate possible causes for transient AVB in dogs.